(1/7 + 1/77 + 1/777) x (0,5 – 1/3 – 1/6)
K
Khách
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
Những câu hỏi liên quan
TT
2
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
7 tháng 4 2015
\(\frac{\frac{1}{77}-\frac{1}{777}-\frac{1}{7951}}{\frac{4}{77}-\frac{4}{777}-\frac{4}{7951}}=\frac{\frac{1}{77}-\frac{1}{777}-\frac{1}{7951}}{4.\left(\frac{1}{77}-\frac{1}{777}-\frac{1}{7951}\right)}=\frac{1}{4}\)
NC
4
![](https://rs.olm.vn/images/avt/0.png?1311)
V
0
![](https://rs.olm.vn/images/avt/0.png?1311)
\(\left(\frac{1}{7}+\frac{1}{77}+\frac{1}{777}\right)\times\left(0,5-\frac{1}{3}-\frac{1}{6}\right).\)
= \(\left(\frac{1}{7}+\frac{1}{77}+\frac{1}{777}\right)\times\left(\frac{6}{12}-\frac{4}{12}-\frac{1}{12}\right)\)
= \(\left(\frac{1}{7}+\frac{1}{77}+\frac{1}{777}\right)\times0\)
= 0
(1/7 + 1/77 + 1/777) x (0,5 - 1/3 - 1/6)
= (1/7 + 1/77 + 1/777) x (1/2 - 1/3 - 1/6)
= (111/777 + 11/777 + 1/777) x (3/6 - 2/6 - 1/6)
= (111/777 + 11/777 + 1/777) x 0
= 0